2009
DOI: 10.4236/jilsa.2009.11001
|View full text |Cite
|
Sign up to set email alerts
|

Towards Real-World Applications of Online Learning Spiral Recurrent Neural Networks

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The authors in [16] claims that the maximum P scales as N/ log(N). More recently, the authors in [17] discussed how to design networks of specific topologies, and how to reach α c values larger than 0.14. Unfortunately, it still finds a bound on the number of limiting behaviours that scale linearly to N. Clearly, the optimal storage problem is still open and how to achieve this optimal storage is still the subject of research [18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [16] claims that the maximum P scales as N/ log(N). More recently, the authors in [17] discussed how to design networks of specific topologies, and how to reach α c values larger than 0.14. Unfortunately, it still finds a bound on the number of limiting behaviours that scale linearly to N. Clearly, the optimal storage problem is still open and how to achieve this optimal storage is still the subject of research [18].…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, Mc Eliece et al (1987), considering only the Hebbian dyadic form for the coupling matrix, found a more severe limitation: the maximum P scales as N /log( N ). In a more recent study, Sollacher et al (2009) designed a network of specific topology, reaching α c -values larger than 0.14, but still maintaining the limit of a linear N dependence of the maximum storage capacity. The storage problem remains an open research question (Brunel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks are widely used in the characterization of nonlinear systems [1][2][3][4][5][6][7], time-varying time-delay nonlinear systems [8] and they are applied in various applications [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%